KERAGAMAN FENOTIPE DAN GEN SIFAT KUALITATIF PADA AYAM KAMPUNG - Sirman Kunuti; Fahrul Illham; Safriyanto Dako (Jambura Journal of Animal Science, 2021)
The research objective was to determine the phenotypic diversity of the qualitative characteristics of Kampung chickens. This research uses a descriptive statistic method. A total of 300 adult (unsex) chickens aged 6 months were used for this study. Qualitative characteristics include: color feather, color pattern, comb shape, fliker, and color variations. The results showed that the gene frequencies of colored feathers and colorless feathers from Kampung chickens were 0.96% and 0,04. The gene frequencies for the color feather pattern were 0.61, 0.43, and 0,03 for the columbian, wild and black color patterns. The gene frequencies for striated and plain hair were: 0.29 and 0.71. The gene frequencies for silver and gold feathers are 0.30, and 0.71%. The Gene Frequencies for Single Comb and Pae are 0.60 and 0.40. The phenotypic frequency of the color pattern of the Kampung chickens was 43.33%, 38.00%, and 12.00%, for wild, Columbia and black pattern. Phenotypic frequency of lurik and plan were: 81.34% and 18.66%. The phenotypic frequency of silver and gold feather were 31,89%, and 68.11%.  The phenotypic frequencies of the comb shape single, pea, rose, and walnuts were 36%, 27,82%, 18,51% dan 17,67%. The population of Paguyaman chickens has a phenotype of colored feathers, the color feather pattern are wild, single comb, yellow shank color, and these characteristics are dominant compared to other characteristics.